Construction methods and management - Nunnally, S. W (Pearson, 2014)
Includes bibliographical references and index; Introduction -- Earthmoving materials and operations -- Excavating and lifting -- Loading and hauling -- Compacting and finishing -- Rock excavation -- Production of aggregate, concrete, and asphalt mixes -- Paving and surface treatments -- Compressed air and water systems -- Foundations -- Wood construction -- Concrete construction -- Concrete form design -- Masonry construction -- Steel construction -- Planning and scheduling -- Construction economics -- Contract construction -- Construction safety and health and equipment maintenance -- Improving productivity and performance